Discovery of the westernmost population of the genus Ansonia Stoliczka (Anura, Bufonidae) with the description of a new species from the Shan Plateau of eastern Myanmar - Quah, Evan S. H.; Grismer, L. Lee; Wood, Perry L. Jr.; Thura, Myint Kyaw; Oaks, Jamie R.; Lin, Aung (Zootaxa, 2019)
A new species of Ansonia is described from the Shan Plateau of Myanmar based on an integrative taxonomic analysis that differentiates it from all other congeners. Molecular phylogenetic analyses based on the mitochondrial genes 12S and 16S rRNA and tRNA-val recover A. kyaiktiyoensis sp. nov. as the sister species to A. inthanon from Thailand but differs from it and other congeners by at least a 5.0% sequence divergence. It is further differentiated by the following combination of morphological characters: (1) maximum SVL 24 mm in males and females; (2) first finger shorter than second; (3) absence of interorbital and tarsal ridges; (4) presence of light-coloured interscapular spot; (5) presence of yellow rictal tubercle; (6) absence of wide, light-coloured patch below eye; (7) presence of large, discrete, bright-yellow submandibular spots along the underside of lower jaw; (8) iris yellow-gold; (9) presence of markings on the snout consisting of streaks below the eye to the lip, and on the canthus rostralis to the nostril; (10) dorsum grey-brown with orange-beige spots, a dark-brown X-shaped marking on the back surrounding the interscapular spot, and dark-coloured markings on rump; (11) fore- and hind limbs with orange-beige cross-bars; and (12) venter light-gray with yellow spotting, especially near flanks and underside of hind limbs. Ansonia kyaiktiyoensis sp. nov. is the westernmost known record for the genus and the only species west of the Salween Basin. Its discovery echoes the increasing number of herpetological discoveries being made in upland regions fringing the Ayeyarwady and Salween Basins.